Obtaining Resveratrol: from Chemical Synthesis to Biotechnological Production - Fan, Enguo; Zhang, Kai; Zhu, Mingzhao; Wang, Qiang (Mini-Reviews in Organic Chemistry, 2010)
Given the pharmacological importance of resveratrol, preparation methods, including plant extraction, chemical synthesis and biotechnological production are evolving rapidly aiming at a large scale production. Plant extraction is the classical method providing major amount of this compound, however, it suffers from low abundance of resveratrol in natural material and environmental, seasonal, or regional variations of natural sources. Complexity of synthetic pathway and the low total yield constrain the industrial application of chemical synthesis. In contrast, biotechnological means offer significantly promising and scalable strategies for resveratrol production while using low-cost and renewable resources. In the present paper, both advantages and disadvantages of these preparation methods as well as the bioavailability and structure-activity relationship of resveratrol have been summarized and discussed aiming to provide valuable information for future improvement of resveratrol production and for searching of a stable and effective resveratrol analogue for therapeutic purposes.
Keywords: biotechnological production